Peran Guru Dalam Menanamkan Karakter Siswa Melalui Literasi Digital Di Era Masyarakat 5.0 - Khania Latifa Zahra; Soybatul Aslamiah Ritonga (Insan Zenius Ilmiah, 2024)
n the era of Society 5.0, digital technology has become an integral part of daily life, including education. This research aims to explore the role of teachers in instilling character in students through digital literacy. The research method used is a literature review employing the library research method. The research results show that teachers play a crucial role in instilling students' character through various digital literacy strategies. The teacher not only serves as a facilitator in the use of technology but also as a role model and guide in shaping students' character, such as integrity, responsibility, cooperation, and critical thinking. The challenges faced include, limited technological resources, a lack of training for teachers and resistance to changes in teaching methods. However, with proper implementation, digital literacy can become an effective tool in instilling character values in students. This study provides recommendations for education practitioners to effectively integrate digital literacy into the curriculum and provide adequate training for teachers to optimally utilize digital technology in shaping students' character.